2014
DOI: 10.1039/c3cp53235f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resonant excitation, pulse duration and intensity on photoelectron imaging of a dianion

Abstract: . (2014) 'E ects of resonant excitation, pulse duration and intensity on photoelectron imaging of a dianion.', Physical chemistry chemical physics., 16 (2). pp. 489-496. Further information on publisher's website:http://dx.doi.org/10.1039/c3cp53235fPublisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Verlet and co-workers have been able to achieve such alignment using pump-probe experiments of two doubly charged dye molecules, pyrromethene 556 (PM 2− ) and doubly deprotonated indigo carmine. 36,[94][95][96] Both dianions consist of a central aromatic system with two terminal sulfonate groups and a π HOMO on the aromatic system, very similar to the diphenyl disulfonate dianion shown in Fig. 3(a).…”
Section: Pump-probe Experiments: Probing Electron Tunneling Throumentioning
confidence: 99%
See 2 more Smart Citations
“…Verlet and co-workers have been able to achieve such alignment using pump-probe experiments of two doubly charged dye molecules, pyrromethene 556 (PM 2− ) and doubly deprotonated indigo carmine. 36,[94][95][96] Both dianions consist of a central aromatic system with two terminal sulfonate groups and a π HOMO on the aromatic system, very similar to the diphenyl disulfonate dianion shown in Fig. 3(a).…”
Section: Pump-probe Experiments: Probing Electron Tunneling Throumentioning
confidence: 99%
“…106 Verlet and co-workers have recently coupled pump-probe experiments with PE imaging to probe the dynamics of MCAs and the effects of the RCB. [94][95][96]107,108 In an experiment on the deprotonated fluorescein dianion, they pumped the dianion to its S 1 excited state within the RCB and observed strong resonant tunneling. 107 They observed that the electron kinetic energies from the resonant tunneling and the tunneling lifetimes are constant when the pump laser was tuned to different vibronic levels of the S 1 state.…”
Section: Pump-probe Experiments: Probing Electron Tunneling Throumentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the electron emission is from a central chromophore so that the final state is in fact an anion which has two localised terminal negative charges and a positive hole at the centre. 24 The RCB can be estimated in much the same manner by treating each charge as a point charge and calculating 40 the interaction of an e -with this total potential. 24 This yields an RCB height of 0.84 eV, which corresponds to κ = 1.31 and this is likely correlated with the delocalised hole.…”
mentioning
confidence: 99%
“…24 The RCB can be estimated in much the same manner by treating each charge as a point charge and calculating 40 the interaction of an e -with this total potential. 24 This yields an RCB height of 0.84 eV, which corresponds to κ = 1.31 and this is likely correlated with the delocalised hole. A key point to note is that the height of the RCB effectively provides a distance measurement between well-localised charge sites in a molecular 50 MCA.…”
mentioning
confidence: 99%